1996
DOI: 10.1007/bf01875587
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding on the secretion of pepsin, trypsin and chymotrypsin in the Atlantic salmon,Salmo salar L

Abstract: Pepsin stored in the stomach mucosa of the Atlantic salmon (Salmo salar L.) increases within two days of the onset of starvation. Trypsin and chymotrypsin in the pyloric caeca/pancreas behave similarly, indicating that when no food is present in the gut, digestive enzymes accumulate in the secretory tissues. As a corollary, trypsin and chymotrypsin activities in the gut contents fell during starvation, indicating that secretion is greatly reduced when food is not present. At the onset of feeding, pepsin is rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…This could be explained considering that the duodenal portion of the intestine is the place where the pancreatic enzymes are released. This should be in agreement with results obtained in different studies comparing herbivorous, omnivorous and carnivorous fishes, which have reported higher trypsin activity in the proximal region of the intestine (Hofer and Schiemer 1981;Bitterlich 1985;Chakrabarti et al 1995;Einarsson et al 1996). Higher trypsin activity in the anterior intestine may enhance the hydrolysis of protein for amino acid absorption, particularly for herbivores and omnivores, which feed on a diet low in protein and nitrogen (Hofer and Schiemer 1981;Bitterlich 1985).…”
Section: Discussionsupporting
confidence: 85%
“…This could be explained considering that the duodenal portion of the intestine is the place where the pancreatic enzymes are released. This should be in agreement with results obtained in different studies comparing herbivorous, omnivorous and carnivorous fishes, which have reported higher trypsin activity in the proximal region of the intestine (Hofer and Schiemer 1981;Bitterlich 1985;Chakrabarti et al 1995;Einarsson et al 1996). Higher trypsin activity in the anterior intestine may enhance the hydrolysis of protein for amino acid absorption, particularly for herbivores and omnivores, which feed on a diet low in protein and nitrogen (Hofer and Schiemer 1981;Bitterlich 1985).…”
Section: Discussionsupporting
confidence: 85%
“…Secretion of protease is proposed to be a response to protein or free amino acids intake (Einarsson et al , 1996; Koven et al , 2002). Consequently, a significant reduction in activity can be directly related to an insufficient supply of these substrates, which should result in poor growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…The constant activity of pepsin in the stomach tissue might be explained by its fast post‐prandial synthesis activity, which did not seem to be affected by lower temperatures. In contrast to trypsin and chymotrypsin, pepsin is rapidly synthesized and secreted with the onset of feeding (Einarsson, Davies & Talbot 1996).…”
Section: Discussionmentioning
confidence: 99%